2015
DOI: 10.1186/1471-2164-16-s8-s3
|View full text |Cite
|
Sign up to set email alerts
|

Disease-associated variants in different categories of disease located in distinct regulatory elements

Abstract: BackgroundThe invention of high throughput sequencing technologies has led to the discoveries of hundreds of thousands of genetic variants associated with thousands of human diseases. Many of these genetic variants are located outside the protein coding regions, and as such, it is challenging to interpret the function of these genetic variants by traditional genetic approaches. Recent genome-wide functional genomics studies, such as FANTOM5 and ENCODE have uncovered a large number of regulatory elements across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 50 publications
(48 reference statements)
1
52
0
3
Order By: Relevance
“…Previous reviews have described a handful of examples of large-effect non-coding alleles underlying Mendelian disorders including beta-thalassemia and polydactyly [21,22]. A systematic analysis of disease variants curated within the Online Mendelian Inheritance in Man (OMIM) and ClinVar databases reported over 27,000 variants connected to Mendelian diseases [23]. While these variants are certain to be of varying quality [24], the authors reported that 29% were either upstream or downstream of their target gene, highlighting the fact that a significant fraction of variation associated to Mendelian disease resides in the non-coding genome.…”
Section: Non-coding Loss-of-function Variationmentioning
confidence: 99%
“…Previous reviews have described a handful of examples of large-effect non-coding alleles underlying Mendelian disorders including beta-thalassemia and polydactyly [21,22]. A systematic analysis of disease variants curated within the Online Mendelian Inheritance in Man (OMIM) and ClinVar databases reported over 27,000 variants connected to Mendelian diseases [23]. While these variants are certain to be of varying quality [24], the authors reported that 29% were either upstream or downstream of their target gene, highlighting the fact that a significant fraction of variation associated to Mendelian disease resides in the non-coding genome.…”
Section: Non-coding Loss-of-function Variationmentioning
confidence: 99%
“…Genome-wide association studies (GWASs) and quantitative trait loci (QTL) studies have been widely applied to the identification and annotation of non-coding mutations [47]. Previous studies have found that Mendelian disease mutations and recurrent cancer somatic mutations are enriched within promoter regions [48]. Enhancers in the human genome are also prone to deactivating mutations that disrupt the binding of transcription factors [49].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, for noncoding variants identifying the target gene and the regulatory function affected is often much more difficult. For example, multiple regulatory functions can be affected by noncoding variants including the binding of TFs [7,8,29], chromatin structure or accessibility [28], DNA methylation [30,31], and 5′ and 3′UTR function [9,32] (Figure 1). …”
Section: Regulatory Variantsmentioning
confidence: 99%